Sleep Alterations in the Population of the Metropolitan Area of Mexico and Their Association with Lifestyle Changes During COVID-19 Confinement - María del Rosario Ayala-Moreno; Paola Andrea Martínez-Serrano; Montserrat Alheli Melgarejo-Gutiérrez; Alma Rosa Hernández-Mondragón; Azucena Martínez-Basila; Araceli Martínez-Coronado; María José Losana-Valencia; Esther Vargas-Medina; Eloisa Colín-Ramírez; Adriana Benítez-Rico (Clocks & Sleep)
Home confinement due to Coronavirus Disease 2019 (COVID-19) led to lifestyle changes that increased sleep disturbances, particularly in areas with higher infection and mortality rates. This study is a retrospective study based on data collected through an online survey conducted during the COVID-19 confinement. It aims to analyze changes in sleep quantity and quality and their association with lifestyle changes in the metropolitan area of Mexico City. A total of 899 adults from this area completed an online questionnaire between June 2020 and February 2021. This study assessed sleep quantity, sleep quality, insomnia symptoms, and lifestyle changes during the confinement period. Results showed that sleep quantity increased (7.10 ± 1.37 vs. 7.43 ± 1.42 h, p < 0.0001), with more participants, especially young adults and women, reporting later bed and wake-up times. The Pittsburgh Sleep Quality Index increased by 1.4 units, with poor sleep quality associated with lifestyle during confinement. Insomnia symptoms, sleep latency, and poor sleep quality also increased, particularly in women. Males and those without chronic comorbidities were less likely to experience poor sleep quality, while tobacco use and later bedtimes increased this risk. This study concludes that, while sleep quantity increased, sleep quality declined, particularly among young adults, women, and those with unhealthy lifestyles. These findings could guide sleep health initiatives tailored to specific lifestyle changes in different population groups.